2018
DOI: 10.1590/2446-4740.04317
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and electromyographic analysis of school children gait with and without load in the backpack

Abstract: Introduction: Excessive load on the backpacks can lead to musculoskeletal injuries and gait alterations. The objective of this study was to analyze the electromyographic (EMG) activity in association to the kinematic during the stance and balance phases of gait performed with and without the use of the backpack. Methods: Twelve volunteers have executed a gait cycle in 3 tasks: without the school backpack (SM), with a backpack with load equivalent to 10% (M10) and 20% (M20) of the body weight (BW). It was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The study strategy is graphed in Figure 1. A total of 27 studies were included: 13 nonrandomized crossover trials13,16,38–48 and 14 randomized crossover trials 49–62. There were 1348 children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study strategy is graphed in Figure 1. A total of 27 studies were included: 13 nonrandomized crossover trials13,16,38–48 and 14 randomized crossover trials 49–62. There were 1348 children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen of the studies were from Asia,13,16,40,44–49,51–54,59,61,62 4 were from Europe,50,55–57 2 from South America,38,58 2 from Africa,41,42 1 from North America,60 1 was from Oceania,39 and 1 from the Middle East 43…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study conducted on primary school students found that the heavier the school backpack was, the higher was the pressure and force distribution under different foot regions [1]. Moreover, carrying school backpacks with loads of more than 10% BW causes changes in the gait kinematics [23].…”
Section: Introductionmentioning
confidence: 99%